Connect [building success through people, purpose, and performance] - Harrell, Keith D. (Tantor Audio : Made available through hoopla, 2007)
Successful motivational speaker Keith Harrell shows how our ability to connect-in our professional lives and personal relationships-is at the core of success. Known well in the corporate world for his energetic and inspirational presentations, Harrell has taken the corporate lecture circuit by storm. He addresses more than 120 events annually for corporate clients such as McDonald's, Microsoft, and American Express. In this latest book, Keith explains that the core of success is the need for people to connect. When individuals connect with the things that they care about-whether it be objectives for the coming year or their relationships outside the workplace-a world of opportunities opens up both professionally and personally. Thought provoking, practical, and energizing, Connect explores the seven core competencies needed to master the art of connecting to heighten productivity and to maximize both personal and professional success.